Herbivory affects male and female reproductive success differently in dioecious Silene latifolia. Issue 1 (14th July 2015) - Litto, Maria; Scopece, Giovanni; Fineschi, Silvia; Schiestl, Florian P.; Cozzolino, Salvatore
Abstract: In dioecious plants, reproductive efforts of male and female plants can be differentially affected by herbivory due to sex‐specific allocation and re‐modulation of resources. Here, we investigate the effects of foliar herbivory by the polyphagous species Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae) on male and female reproductive traits of Silene latifolia (Poir.) (Caryophyllaceae). We set up experimental populations of male and female control and Spodoptera ‐infested plants and estimated flower morphology and phenology, and plant reproductive success. Herbivory did not affect floral traits involved in visual signalling to pollinators (flower size). Female reproductive success did not differ between Spodoptera ‐infested and control plants in terms of seed set and seed germination. On the other hand, Spodoptera ‐infested male plants produced fewer flowers than male control plants and maintained fewer flowers during flowering peaks. By experimental reduction in male flower number, we showed that male flower number is directly correlated with male reproductive success (pollen export to female flowers). This strongly suggests that male reproductive success is reduced after herbivory, whereas female reproductive success remains unaffected. The fact that females are more tolerant against herbivory is in accordance with sexual selection theory, which predicts that females, in contrast to males, are not selected for maximum investment in reproductive traits such as floral signalling, and should thus be more flexible in the allocation of resources.